2017
DOI: 10.1108/rpj-10-2015-0148
|View full text |Cite
|
Sign up to set email alerts
|

Development of CNTs-filled photopolymer for projection stereolithography

Abstract: Purpose Polymeric parts produced by 3D stereolithography (SL) process have poorer mechanical properties as compared to their counterparts fabricated via conventional methods, such as injection or compression molding. Adding nanofillers in the photopolymer resin for SL could help improve mechanical properties. This study aims to achieve enhancement in mechanical properties of parts fabricated by SL, for functional applications, by using well-dispersed nanofillers in the photopolymers, together with suitable pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…The main concern when printing via vat photopolymerization is the high viscosity of the composite resin and the light scattering produced by the filler particles. For instance, CNTs are strong UV absorbers; this presents problems when curing the photopolymer resin (Choong et al, 2020;Eng et al, 2017). Hengky et al (Eng et al, 2017) suggested that using conductive nanoparticles such as CNT in SLA could provide enhanced mechanical properties, electrical and thermal conductivity.…”
Section: Vat Photopolymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main concern when printing via vat photopolymerization is the high viscosity of the composite resin and the light scattering produced by the filler particles. For instance, CNTs are strong UV absorbers; this presents problems when curing the photopolymer resin (Choong et al, 2020;Eng et al, 2017). Hengky et al (Eng et al, 2017) suggested that using conductive nanoparticles such as CNT in SLA could provide enhanced mechanical properties, electrical and thermal conductivity.…”
Section: Vat Photopolymerizationmentioning
confidence: 99%
“…For instance, CNTs are strong UV absorbers; this presents problems when curing the photopolymer resin (Choong et al, 2020;Eng et al, 2017). Hengky et al (Eng et al, 2017) suggested that using conductive nanoparticles such as CNT in SLA could provide enhanced mechanical properties, electrical and thermal conductivity. Particle alignment accomplished while printing is still something that is not fully understood.…”
Section: Vat Photopolymerizationmentioning
confidence: 99%
“…[ 121 ] These materials are usually added to improve the mechanical properties of the final product, [ 122 ] but they can also be used to add new proprieties to the resin, such as thermal resistance, electrical properties, cell viability and others. [ 123 ] In stereolithography, different types of nanomaterials have been mixed in photopolymer resins such as clay, [ 122,124 ] carbon nanotubes (CNTs) and multiwalled carbon nanotubes (MWCNTs), [ 125–127 ] graphene, [ 128 ] nanocellulose crystal (CNC), [ 52,129 ] nanosilicates, [ 130 ] and many others.…”
Section: Nanoparticles In Stereolithography: Treatments Viscosity and Light Propertiesmentioning
confidence: 99%
“…In a similar work, researchers are advanced the mechanical properties of polymer parts by exfoliating and homogeneously dispersing of montmorillonite nanoclays (plate-shaped) into the photocurable resin via several mixing steps. They achieved significant increases at elongation by more than 100% and enhanced the tensile stress and Young’s Modulus in the x-y plane (Eng et al , 2017). In addition, other researchers three-dimensional printed graphene oxide-based nanocomposite without surface modification.…”
Section: Introductionmentioning
confidence: 98%
“…They used nano silica fillers for modifying the light scattering characteristics of the resin and they succeed to reduce curing time from 4 s to 0.7 s for each layer. In another study, Eng et al (2017) improved the mechanical properties such as tensile strength up to 70% and elongation up to 46% of Stereolithography (SLA) printed photo polymer by adding carbon nanotubes into the resin. In a similar work, researchers are advanced the mechanical properties of polymer parts by exfoliating and homogeneously dispersing of montmorillonite nanoclays (plate-shaped) into the photocurable resin via several mixing steps.…”
Section: Introductionmentioning
confidence: 99%